Analisis SWOT Dalam Penentuan Strategi Untuk Meningkatkan Kinerja Frontliner Di Bank Sumut KCP Syariah Lubuk Pakam - Regi Anika; Tuti Anggraini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Every financial institution has a frontliner who serves as a front guard or sequencer and provides information about banking as well as initial impressions of a bank. Due to the rapid development of the banking industry, PT. Bank Sumut KCP Syariah Lubuk Pakam must determine ways to improve the performance of frontline employees so they can compete with other banks. The problems raised in this research relate to how PT. Bank Sumut KCP Syariah Lubuk Pakam chose an approach to improve frontliner performance through SWOT analysis. Frontline Officers must have the knowledge and expertise in their profession to carry out their primary duties effectively. To do this, they must receive training and support that starts from the individual's outer appearance and continues within, so that when providing consumers receive fast, efficient and polite service, resulting in high customer satisfaction. This research uses qualitative methods and descriptive research design. SWOT analysis is used to apply qualitative and descriptive analysis to arrive at research conclusions. Based on the results of the Cartesian diagram, the institution is in Quadrant I, actively implementing a Growth-Oriented Strategy and supporting this strategy.